Studi Deskriptif Kuantitatif Mengenai Anxiety pada Pelaku Cigarette Addiction di SMA N 1 Kecamatan Bukik Barisan - Tesa Anggraini; Hinal Muazin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Anxiety is a common problem that can affect a person's physical and psychological changes, especially in cigarette addiction perpetrators. Addiction or addiction is an unhealthy behavioral condition that causes physical or mental dependence on something so that it has an impact on the behavior of the person who experiences it. This study aims to describe the level of anxiety in addiciton cigarette perpetrators at SMA N 1 Bukik Barisan. The study used a descriptive quantitative approach with an accidental sampling technique, with a sample of 12 students aged 15-18 years. Data was collected through the Beck Anxiety Inventory (BAI) questionnaire and analyzed using the SPSS 22 program. The results of the normality test in this study showed 0.079 (p>0.05), so it can be said that the anxiety variable has a normal data distribution. The results stated that the description of the level of anxiety in cigarette addiction perpetrators at SMA N 1 Bukik Barisan was included in the mild category.